Implementation of Fuzzy Linguistic Quantifier and Analytic Hierarchy Process in Decision Support Systems (Case Study: Exemplary Employee Selection ) - Rusdi Efendi; Gustian Aidil Fitri (Annual Research Seminar (ARS), 2015)
To Make the selection based on potential model employee that he had not an easy thing, especially if conducting assessment involving people (Group Decision Support System). Sometimes a leader or manager of the company only chose an exemplary employee based on the recommendation of other employees. What if this exemplary employee assessment to be done by more than one person, let alone carried out by a division manager or supervisor with the reason the parties that often interact directly with employees so as to provide a more objective assessment.In this study the variables that are used to perform calculations on model employee 4 pieces, namely: performance, discipline, loyalty, and presence. The assessment process begins weighting to each variable by using fuzzy linguistic quantifier levels while using Analytic Hierarchy Process (AHP). The end result of this research is in the form of an exemplary employee levels where persantase of each variable is not an average value as is commonly done, but based on the interest factor of each variable.